Evaluasi Program Pelatihan bagi Guru Di Sdn-2 Panarung dengan Model Countenance Stake - Dina Mardiana (Jurnal Pendidikan Edutama, 2023)
Abstract: This educational evaluation research aims at evaluating the training program in PKM-PDPSU activity carried out at SDN-2 Panarung Palangkaraya. The training was provided to improve the ability of nine teachers at the primary school to apply the education content of humanist literacy in language learning in order to form Pancasila-uphold generation in students through PKM-PDPSU activity. The evaluation of the program was carried out by the author as an evaluator with a team of experts using the Countenance Stake model. Data were collected using techniques such as observation, document review, and interview. Then, the data were analyzed using a case study analysis technique by the descriptive qualitative method. From the result of the evaluation, an average score of 4.8 was obtained and categorized as a good quality of the implementation in the educational program. By the evaluation activity, the evaluator team has proven that the evaluation of the countenance stake model can be carried out on an educational training program by a lecturer team from the university in the community service activity (PKM).  Keywords: education evaluation, countenance stake, training, primary school teachers  Abstrak: Penelitian evaluasi pendidikan ini bertujuan untuk melakukan evaluasi terhadap program pelatihan dalam kegiatan PKM-PDPSU yang dilaksanakan di SDN-2 Panarung Kota Palangkaraya. Pelatihan diberikan untuk meningkatkan kemampuan sembilan orang guru di sekolah dasar tersebut untuk mengaplikasikan muatan pendidikan literasi humanis dalam pembelajaran bahasa guna membentuk tunas Pancasila pada diri peserta didik melalui kegiatan PKM-PDPSU. Evaluasi program dilakukan oleh penulis sebagai evaluator bersama tim ahli dengan menggunakan model countenance Stake. Data dikumpulkan dengan menggunakan teknik observasi, telaah dokumen, dan wawancara, selanjutnya dianalisis dengan teknik analisis studi kasus dalam metode deskriptif kualitatif. Dari hasil evaluasi program diperoleh nilai rata-rata 4,8 yang berkategori baik untuk kualitas pelaksanaan program pendidikan. Pada kegiatan evaluasi program pendidikan ini, tim evaluator telah membuktikan bahwa evaluasi model countenance Stake dapat dilakukan pada sebuah program pelatihan pendidikan yang dilaksanakan oleh tim dosen dari perguruan tinggi dalam kegiatan pengabdian kepada masyarakat (PKM). Kata Kunci: evaluasi pendidikan, countenance Stake, pelatihan, guru sekolah dasar